Path loss through pine forest around beach for wireless sea wave energy sensor network - Supachai Phaiboon (2018)
This paper presents an empirical path loss model through forest for measuring sea wave energy using 2.4 GHz wireless sensor network (WSN). The empirical path loss model was determined from measurement campaign by using 18 dBm transmitter and the receivers with a low noise amplify. The conventional path loss models for forest environments were carried out such as Weissberger, ITU-R, COST 235 and Torrico models. From the results it is found that the proposed model provides a good agreement and is used for planning WSN. © (2012) Trans Tech Publications, Switzerland.